The Effect of Direct Compensation and Work Motivation on Employee Performance: Study at A Government Office in Bandung Regency - Awal Purnomosidi; M. Sidik Priadana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
This study aimed to determine the effect of direct compensation and work motivation on employee performance—this study conduct by taking a sample of employees at one of the government offices in Bandung Regency. The research method used is a qualitative method with a total of 50 respondents using path analysis techniques. As for his research results, there is a significant effect of direct compensation and work motivation on employee performance either partially or simultaneously. Direct compensation and work motivation together affect employee performance by 64.04%. The proportionate amount of influence caused by other variables other than direct compensation and work motivation is 35.98%. The study results recommend that direct compensation and efforts to increase work motivation should always increase performance according to what has been determined.